Exploring Serendipity and Impulse Buying: Insights through Regulatory Focus Theory - Son, Junghwa; Yoon, Hye Jung (Journal of Ecohumanism, 2024)
The objective of this study is to examine the impact of perceived serendipity on impulse buying in the context of live streaming commerce, with a focus on the moderating effect of price on this relationship. A total of 205 usable datasets were collected in Korea. All four proposed hypotheses were supported, and perceived serendipity was found to have a positive effect on both impulse buying intention and impulse buying. High-priced products amplified the impact of perceived serendipity on impulse buying. The findings of this study offer significant contributions to both academic research and practical applications.